Certain Kummer’s Matrix Function of Two Complex Variables under Certain Differential and Integral Operators: R.A. Rashwan, M.S. Metwally, M.T. Mohamed, A. Shehata - Team, Support (Thai Journal of Mathematics, 2013)
The main aim of this paper is to define and study of a new matrix function, say, the Kummer’s matrix function of two complex variables. The domain of regularity, integral form, matrix recurrence relation and several new results on this function are established. We study the operation of differential operators of Kummer’s matrix function that solutions of certain matrix differential equations have been obtained. Finally the study of the integral operators with of Kummer’s matrix function is investigated.